Safety and efficacy of AK0529 in respiratory syncytial virus-infected infant patients: A phase 2 proof-of-concept trial - (:unkn) unknown (My University, 2023)
Background: Respiratory syncytial virus (RSV) infection is a cause of substantial morbidity and mortality in young children. There is currently no effective therapy available. Methods: This was a Phase 2 study of the oral RSV fusion protein inhibitor AK0529 in infants aged 1–24 months, hospitalized with RSV infection. In Part 1, patients (n = 24) were randomized 2:1 to receive a single dose of AK0529 up to 4 mg/kg or placebo. In Part 2, patients (n = 48) were randomized 2:1 to receive AK0529 at 0.5, 1, or 2 mg/kg bid or placebo for 5 days. Sparse pharmacokinetic samples were assessed using population pharmacokinetics modelling. Safety, tolerability, viral load, and respiratory signs and symptoms were assessed daily during treatment. Results: No safety or tolerability signals were detected for AK0529: grade ≥3 treatment-emergent adverse events occurring in 4.1% of patients in AK0529 and 4.2% in placebo groups, respectively, and none led to death or withdrawal from the study. In Part 2, targeted drug exposure was reached with 2 mg/kg bid. A numerically greater reduction in median viral load with 2 mg/kg bid AK0529 than with placebo at 96 h was observed. A −4.0 (95% CI: −4.51, −2.03) median reduction in Wang Respiratory Score from baseline to 96 h was observed in the 2 mg/kg group compared with −2.0 (95% CI: −3.42, −1.82) in the placebo group. Conclusions: AK0529 was well tolerated in hospitalized RSV-infected infant patients. Treatment with AK0529 2 mg/kg bid was observed to reduce viral load and Wang Respiratory Score. Clinical Trials Registration: NCT02654171.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Social Sciences and Humanities; Sociology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Klinik Tıp; İmmünoloji; Sosyal Bilimler Genel; SOLUNUM SİSTEMİ; BULAŞICI HASTALIKLAR; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Life Sciences (LIFE); Social Sciences (SOC); CLINICAL MEDICINE; IMMUNOLOGY; SOCIAL SCIENCES, GENERAL; RESPIRATORY SYSTEM; INFECTIOUS DISEASES; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Epidemiyoloji; Akciğer ve Solunum Tıbbı; Halk, Çevre ve İş Sağlığı; Bulaşıcı hastalıklar; Epidemiology; Pulmonary and Respiratory Medicine; Public Health, Environmental and Occupational Health; Infectious Diseases; AK0529; fusion inhibitor; infants; respiratory syncytial virus (RSV); ziresovir